2004
DOI: 10.1258/0004563042466884
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinogen

Abstract: Fibrinogen is the major plasma protein coagulation factor. Low plasma fibrinogen concentrations are therefore associated with an increased risk of bleeding due to impaired primary and secondary haemostasis. Fibrinogen is a classical positive acute-phase reactant protein and is an independent predictor of coronary heart disease events. This review considers available methods for measurement of fibrinogen and makes recommendations as to their appropriate use.Total clottable fibrinogen assays are the definitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 22 publications
2
141
1
2
Order By: Relevance
“…It consists of two sets of three disulphide-bridged chains (Aa, Bb, and g) of 610, 461, and 411 amino acid residues, respectively. Structure, heterogeneity, function and assays were all reviewed else-where [177][178][179][180]. Western blot immunoassay showed that fibrinogen, among other plasma proteins, is highly susceptible to attack by oxidants [181].…”
Section: Fibrinogenmentioning
confidence: 99%
“…It consists of two sets of three disulphide-bridged chains (Aa, Bb, and g) of 610, 461, and 411 amino acid residues, respectively. Structure, heterogeneity, function and assays were all reviewed else-where [177][178][179][180]. Western blot immunoassay showed that fibrinogen, among other plasma proteins, is highly susceptible to attack by oxidants [181].…”
Section: Fibrinogenmentioning
confidence: 99%
“…Thus, not all circulating fi brinogen is functional or clottable. As the tissue repair process takes place, the fi brin plug is digested by fi brinolytic enzymes (Lowe et al , 2004 ). On the one hand, low levels of plasma fi brinogen are associated with an increased risk for bleeding, as platelet aggregation as well as fi brin plug formation is impaired.…”
Section: Thrombosismentioning
confidence: 99%
“…Platelet adhesion and activation are thus regulated by specifi c proteins on the platelet surface, and fi brinogen as well as fi bronectin plays a fundamental role in the coagulation process (Ni et al , 2000 ;Lowe et al , 2004 ). Fibrin assembly (through the coagulation pathway and involvement of the platelets) from fi brinogen proceeds in a highly ordered fashion.…”
Section: Thrombosismentioning
confidence: 99%
See 2 more Smart Citations